Where's the GPS? navigating treatment with co-existing problems. A reflective journey amongst graduate practitioners. Issue 6 (1st November 2016) - Shepherd, Robin-Marie; Newcombe, David A.
Abstract: This paper examines reflective portfolios of graduate students studying co-existing problems (CEP) within an alcohol and drug studies programme in New Zealand. The methodology employs Todd's principles of treating co-existing disorders (culture, management, engagement, assessment, integrated care, well-being and management). The metaphor, a GPS, is employed in the title to describe how Todd's principles are used as a GPS to help navigate the murky waters of working with this specialised client population. The principles, allocated as themes within the portfolios, highlight how these principles are reflected upon within their workplace. Culture and engagement principles were the most endorsed themes within the portfolios. The reflective portfolios also allowed us to reflect upon the ongoing process of curriculum development for this specialised client population.